The Middle Eastern Culture and it's Representation in Walt Disney Pictures Movie "Aladdin" (2019) - Firda Ayuningtiyas; Ali Mustofa (Humanitatis : Journal of Language and Literature, 2021)
This article examined how Disney presents Middle Eastern culture in the film Aladdin (2019). To analyze the first research question in this article, the author used Cultural studies theory by Stuart Hall, which further examines the Middle Eastern cultural representations that may be related to the power shown in this film. In the first research question, there are 2 sub-chapters, namely the location setting used for the making of this film. It is known that the filming location of this film is built to resemble the Middle East region, and the costumes worn by the main characters in the film look like traditional Middle Eastern costumes. The second research question is about the influence of Western ideology on films. This question will address how Disney influences viewers' perspectives in the Middle East. The author has a statement that the character Princess Jasmine was created by Disney (west), which is a character that represents modern women. To examine the second question the author uses the theory of Orientalism by Edward said.